Reconsidering Mandatory Audit Firm Rotation in Indonesia: Perspectives from Large, Medium, and Small Audit Firms - Fitriany Fitriany; Viska Anggraita; Sandra Aulia; Tarko Sunaryo; Rio F Kiantara (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to assess the perceptions of large, medium, and small accounting firms regarding the reconsidering of mandatory audit firm rotation (MAFR) in Indonesia, considering its impact on independence, professional skepticism, new perspectives, familiarity threats. Methodology/Approach: This study used a quantitative approach, using questionnaires from auditors from three groups of accounting firms. These questionnaires were analyzed using the Kruskal-Wallis test and Dunn's post-hoc test to identify significant differences between groups. Findings: The study, with 235 respondents, showed that perceptions of MAFR in Indonesia vary across accounting firms. Small accounting firms support MAFR because they believe it maintains independence, strengthens professional skepticism, and opens up opportunities for new clients. Medium accounting firms are moderate, considering both the legitimacy benefits and the costs of rotation. Conversely, Big Four accounting firms view firm rotation as less necessary, as they rely on partner rotation, global reputation, and a strong internal quality control system. Practical Implications: Although perceptions of MAFR differ across accounting firm groups, MAFR should continue to be implemented with the support of mechanisms such as comprehensive audit documentation and effective knowledge transfer to achieve the benefits of rotation without compromising audit quality. Originality/Value: No research has been found comparing the perceptions of large, small, and medium-sized auditors regarding MAFR in terms of independence, professional skepticism, and audit costs, and statistically testing the relevance of MAFR in the Indonesian context following the revocation of the MAFR policy.